Effects of arbuscular mycorrhizal fungi on a fallow enriching tree (Macaranga denticulata) - Youpensuk S. (2014)
Macaranga denticulata is a fallow enriching species that is important in upland agriculture in parts of northern Thailand. The root zone of this tree supports a high biodiversity of arbuscular mycorrhizal (AM) fungi and it has been postulated that these are important for Macaranga to rapidly establish in disturbed fields. To evaluate this, seedlings were inoculated with spores of AM fungi (Glomus spp., G. fasciculatum, Acaulospora spp. and mixed species of AM fungi) collected from the field, and then grown without P fertilizer. Growth of the host was compared with plants grown concurrently at six rates of phosphorus application (0 to 150 mg P/kg soil). The experiments were conducted in pots containing 5 kg sterilized soil. Arbuscular mycorrhizal inoculation increased height and plant dry weight. Dry weights of M. denticulata inoculated with Acaulospora spp. or mixed species of AM fungi were equivalent to uninoculated plants given 150 mg P/kg soil, whereas plants inoculated with Glomus spp and G. fasciculatum were similar to those with 25 mg P/kg soil. Nutrient contents of plant inoculated with Acaulospora spp. and mixed species of AM fungi were higher than plants inoculated with Glomus spp and G. fasciculatum. Root colonization of plants inoculated with Acaulospora spp. and mixed species of AM fungi was not significantly different, and was higher than other inoculated treatments. These experiments have shown that M. denticulata is dependent on AM fungi for rapid growth in a low P soil. Acaulospora morrowiae appeared to be the dominant species sporulating in root zones of plants inoculated with either Acaulospora spp. or mixed species of AM fungi. Further work is required to identify the most effective AM species for M denticulata since the abundance of AM spores in the root zone may not be directly related to the effectiveness of root colonization in nutrient uptake of the tree.